The Moderating Effect of Audit Quality on CEO Compensation and Tax Avoidance: Evidence from Tunisian Context - Jihene, Ferchichi; Moez, Dabboussi (International Journal of Economics and Financial Issues, 2019)
The purpose of this paper is to examine the effect of CEO compensation on corporate tax avoidance. It is also investigated the moderating effect of corporate governance, especially the audit quality on this association. We use a sample of 67 firms listed on the Tunisian stock exchange from 2013 to 2016. Based on GLS regression models, we find that there is a positive and significant relationship between CEO compensation and corporate tax avoidance. This result advances that managers are willing to engage in risky activities that provide them additional compensation by extracting rents from tax-saving positions. However, we find a negative association between variable CEO compensation and tax avoidance in well-audited firms, supporting the moderating effect of audit quality on the relation between CEO compensation and tax avoidance. These findings suggest that audit quality is efficient corporate governance, while protecting users against the opportunistic and fraudulent actions of managers. Keywords: Tax Avoidance, CEO Compensation, Audit Quality. JEL Classifications: G30, G32, G34 DOI: https://doi.org/10.32479/ijefi.7355